Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Numbered Heads Together untuk Meningkatkan Karakter Gotong Royong - Cahyani, Sekar Ayu; Irianto, Dede Margo; Furnamasari, Yayang Furi (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to determine the effect of implementing the NHT type cooperative learning model on students' mutual cooperation character and the difference in influence between classes that apply the NHT type cooperative learning model and classes that apply the TGT type cooperative learning model. This research applies a quasi-experimental method with a quantitative approach using non-equivalent control group design. With a research sample of 25 students in class VA and 25 students in class VC at SDN 052 Cisaranten Wetan Gedebage for the 2023/2024 academic year. The data collection technique used is a test. The data analysis technique in this research is by testing prerequisite analysis and hypothesis testing. The results of the research show that the effect of implementing the NHT type cooperative learning model on students' mutual cooperation character has increased moderately in the experimental class. The effect of implementing the TGT type cooperative model on the mutual cooperation character of students in the control class experienced a slight increase. The difference in improvement can be seen as shown by the results of the independent sample t-test which confirms that there is a difference in influence between the experimental class and the control class.